Lithium metal negative plate, preparation method thereof and battery
By using PCN-250 derivative material coating on the negative electrode of lithium metal batteries, the problem of gas production and expansion during the cycle of lithium metal batteries is solved, the safety and stability of the battery are enhanced, and the uniform deposition and structural stability of lithium ions are achieved.
Patent Information
- Application Number
- CN202510779571.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-11
- Publication Date
- 2025-09-12
AI Technical Summary
Lithium metal batteries produce a large amount of side reaction gases during the cycle, causing the battery cells to swell, posing a safety hazard. Lithium dendrites may also cause safety issues such as thermal runaway and internal short circuits.
A coating containing PCN-250 derivative materials is used. The coating contains a metal-organic framework material with ester azobenzene groups. The porosity and pore size are designed to adsorb side reaction gases, and the structure undergoes structural transformation under mechanical pressure to stabilize lithium ion deposition. The safety performance is improved by combining lithium-philic metal elements and conductive agents.
It effectively absorbs side reaction gases, prevents battery cell swelling, enhances the safety performance and cycle stability of lithium metal batteries, uniformly deposits lithium ions, and improves the mechanical and chemical stability of the battery.
Smart Images

Figure CN120637392A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of batteries, and in particular to a lithium metal negative electrode sheet, a preparation method thereof, and a battery. Background Art
[0002] The metallic lithium anode has an extremely high theoretical capacity (3860 mAh g) which is 10 times that of the commercial graphite anode. -1 ) and the lowest chemical potential (-3.04V relative to the standard hydrogen electrode), have long been considered the "holy grail" of all anode materials. However, before lithium metal anodes can be put into practical use, key scientific issues need to be resolved: 1. Interfacial side reactions; 2. Lithium dendrites; 3. Volume effects; and 4. Safety issues.
[0003] Because lithium metal batteries use pure lithium in their negative electrodes, the impact of safety incidents is far greater than that of conventional battery systems. During lithium ion deposition, the uneven electric field distribution on the electrode surface leads to uneven lithium ion flow, which in turn causes uneven lithium deposition and ultimately the formation of lithium dendrites. These dendrites can penetrate the separator and trigger a series of safety issues, such as thermal runaway and internal short circuits. Furthermore, metallic lithium is highly chemically and electrochemically reactive, meaning it continuously reacts with nearly all liquid electrolytes at the interface. This can lead to the generation of significant gasses within the battery, causing the battery cell to swell during cycling, posing a safety hazard. Summary of the Invention
[0004] In view of this, the present invention is dedicated to providing a lithium metal negative electrode sheet and a preparation method thereof and a battery to solve the problem of gas production and expansion of lithium metal batteries in the prior art.
[0005] In order to solve the above technical problems, this application is implemented as follows:
[0006] The present invention provides a lithium metal negative electrode sheet, comprising a metal substrate and a coating provided on at least one surface of the metal substrate along a thickness direction; the coating comprises a metal organic framework material;
[0007] The metal organic framework material includes a PCN-250 derivative material, and the PCN-250 derivative material has an ester azobenzene group.
[0008] Optionally, the porosity of the metal organic framework material is 50% to 70%. Optionally, the pore size of the metal organic framework material is 0.6 to 1.5 nm.
[0009] Optionally, the coating further contains a lithium-philic metal element; optionally, the lithium-philic metal element includes at least one of zinc, tin, magnesium and aluminum; optionally, the atomic number ratio of the lithium-philic metal element to the iron element in the PCN-250 derivative material is (0.01-0.03): (0.56-1.5).
[0010] Optionally, the coating further includes a binder and a conductive agent; optionally, the mass ratio of the metal organic framework material, the binder and the conductive agent in the coating is (0.7-0.9): (0.1-0.2): (0.05-0.1); optionally, the binder includes polyvinylidene fluoride; and the conductive agent includes conductive carbon black.
[0011] Optionally, the coating has a thickness of 5 to 50 μm.
[0012] A second aspect of the present invention further provides a method for preparing a lithium metal negative electrode sheet, comprising the following steps:
[0013] S1, mixing PCN-250 material, carboxylic acid compound, hydroxyl-containing volatile solvent and water, performing pore-forming reaction and esterification reaction to obtain PCN-250 derivative material;
[0014] S2. Prepare a slurry containing the derivative material of PCN-250, and form a coating on the base film with the slurry.
[0015] Optionally, in step S1, the mass ratio of the PCN-250 material, the carboxylate, the hydroxyl-containing volatile solvent and water is (3-8): (2-6): (6-12): (10-20); optionally, the carboxylic acid compound includes carboxylate and / or carboxylic acid; optionally, the carboxylate includes acetate, preferably, the acetate includes at least one of zinc acetate, tin acetate, magnesium acetate and aluminum acetate; optionally, the carboxylic acid includes acetic acid; optionally, the hydroxyl-containing volatile solvent includes at least one of methanol, ethanol and propanol.
[0016] Optionally, in step S2, the method for preparing the slurry containing the PCN-250 derivative material includes stirring the PCN-250 derivative material, a binder, a conductive agent, and a solvent; optionally, the solvent includes dimethylformamide and / or N-methyl-2-pyrrolidone.
[0017] Optionally, in step S1, the environmental conditions of the pore-forming reaction are a closed environment, the temperature of the pore-forming reaction is 80-95°C, and the time of the pore-forming reaction is 1-4 hours; optionally, in step S1, the temperature of the esterification reaction is 110-140°C, and the time of the esterification reaction is 2-4 hours.
[0018] A third aspect of the present invention provides a battery comprising a negative electrode, wherein the negative electrode comprises the aforementioned lithium metal negative electrode and / or a lithium metal negative electrode prepared according to the aforementioned preparation method. Through the above technical solution, the beneficial technical effects of the present invention are as follows:
[0019] (1) The lithium metal negative electrode provided in the present invention includes a metal substrate and a coating made from a derivative material of PCN-250. The derivative material of PCN-250 has an ester azobenzene group. The derivative material of the metal organic framework material PCN-250 has a stable pore and an adjustable pore size. It can adsorb byproducts produced by side reactions without affecting ion transmission, preventing the lithium metal battery from producing a large amount of side reaction gas in the late cycle, thereby solving the safety hazard of battery cell swelling caused by gas production. In addition, the derivative material of PCN-250 will undergo a structural transformation under mechanical pressure. Due to the flipping of the azobenzene group in the material, its structure changes from square to rhombus. After the pressure affects the derivative material of PCN-250, it can generate pressure inside the pore after the electrolyte enters the internal pore, changing its structure from rhombus to square, and has good mechanical properties. In addition, in the ester azobenzene group of the derivative material of PCN-250, the oxygen atom in the ester group is connected to the carbon atom through a covalent bond, so that the ester azobenzene has better chemical stability. In addition, the introduction of lithiophilic elements into the coating can act as a bridge to guide the uniform deposition of lithium ions in PCN-250 derivatives with a larger surface area, thereby enhancing the safety and cycle stability of lithium metal batteries.
[0020] (2) The preparation method of the lithium metal negative electrode provided by the present invention uses a common hydroxyl-containing volatile solvent and water to react with the PCN-250 material to form a pore, and then adds a carboxylic acid compound. While the PCN-250 material forms pores, the azobenzene group therein also reacts with the hydroxyl group of the hydroxyl-containing volatile solvent to generate hydroxyazobenzene. When the high-temperature reaction is carried out in a closed container, the hydroxyl-containing volatile solvent and water will evaporate at a certain temperature, and the volatilized gas cannot be discharged. The gas will expand the pores that originally had a certain diameter, and the expanded pores will absorb more gas. Finally, the generated hydroxyazobenzene group will also react with the carboxyl group of the carboxylic acid compound to generate an ester group (COOR'). The oxygen atom in the ester group is connected to the carbon atom through a covalent bond, so that the ester azobenzene has better chemical stability.
[0021] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention, but do not constitute a limitation of the present invention.
[0023] Figure 1 Shown is the structural formula of the derivative material of PCN-250. DETAILED DESCRIPTION
[0024] The present invention discloses a lithium metal negative electrode sheet, a method for preparing the same, and a battery. Those skilled in the art may refer to the contents herein and appropriately modify the process parameters to achieve the desired results. It is particularly important to note that all similar substitutions and modifications apparent to those skilled in the art are considered encompassed by the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel will readily be able to modify or appropriately alter and combine the methods and applications described herein to implement and apply the technology of the present invention without departing from the content, spirit, and scope of the present invention.
[0025] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms can mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A can include a single element or multiple elements. Item B can include a single element or multiple elements. Item C can include a single element or multiple elements.
[0026] The endpoints of the ranges and any values disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered to be specifically disclosed herein.
[0027] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0028] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0029] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0030] In order to solve the problem of gas expansion of lithium metal batteries in the prior art, the present invention adopts the following technical solutions:
[0031] The present invention provides a lithium metal negative electrode sheet, comprising a metal substrate and a coating provided on at least one surface of the metal substrate along a thickness direction; the coating comprises a metal organic framework material;
[0032] The metal organic framework material includes a PCN-250 derivative material, and the PCN-250 derivative material has an ester azobenzene group.
[0033] The lithium metal anode sheet of the present invention comprises a metal substrate and a coating made from a PCN-250 derivative material. The PCN-250 derivative material has ester azobenzene groups. The PCN-250 derivative material, a metal-organic framework material, has stable pores and adjustable pore size, allowing it to adsorb byproducts produced by side reactions without affecting ion transport. This prevents the lithium metal battery from generating large amounts of side reaction gases in the late stages of cycling, thereby addressing the safety hazard of cell bulging caused by gas production. Furthermore, the PCN-250 derivative material undergoes a structural transformation under mechanical pressure. Due to the flipping of the azobenzene groups in the material, its structure changes from square to rhombus. Once under pressure, the PCN-250 derivative material can generate pressure within the internal pores after the electrolyte enters, transforming its rhombus structure back to square, resulting in excellent mechanical properties. Furthermore, in the ester azobenzene groups of the PCN-250 derivative material, the oxygen atom in the ester group is covalently bonded to the carbon atom, giving the ester azobenzene improved chemical stability.
[0034] In this application, “PCN-250” refers to a metal organic framework material with Fe as the metal and 3,3′,5,5′-azobenzenetetracarboxylic acid as the ligand, and its CAS number is 1771755-22-6.
[0035] "PCN-250 derivative materials" mainly refer to materials that have ester azobenzene groups introduced into PCN-250. Specifically, the introduction method can be to react the azobenzene group in the metal organic framework material PCN-250 with the hydroxyl group to generate hydroxyazobenzene, and then react the hydroxyazobenzene with the carboxyl group to generate the ester azobenzene group. The structural formula of the PCN-250 derivative material is as follows: Figure 1 As shown in the chemical formula, R is hydrogen.
[0036] According to the present invention, the porosity of the metal organic framework material can be 50% to 70%. In the present invention, the porosity of the metal organic framework material is suitable for adsorbing more gas and solving the potential safety hazard caused by swelling of the battery cell due to gas production. As an example, the porosity of the metal organic framework material can be any value among 50%, 52%, 55%, 58%, 60%, 62%, 65%, 68% and 70%, or any value within the range of any two of the above values. In the present invention, if the porosity of the metal organic framework material is too large, it will affect the transmission of lithium ions; if the porosity of the metal organic framework material is too small, it will result in limited adsorption of gas.
[0037] According to the present invention, the pore size of the metal organic framework material can be 0.6 to 1.5 nm. In the present invention, the pore size of the metal organic framework material is suitable for adsorbing the most harmful gases. As an example, the pore size of the metal organic framework material can be any value among 0.6 nm, 0.7 nm, 0.8 nm, 0.9 nm, 1 nm, 1.1 nm, 1.2 nm, 1.3 nm, 1.4 nm and 1.5 nm, or any value within the range of any two of the above values. In the present invention, if the pore size of the metal organic framework material is too large, it will affect the transmission of lithium ions; if the pore size of the metal organic framework material is too small, it will result in limited adsorption of gases.
[0038] According to the present invention, the coating layer may further contain a lithium-philic metal element.
[0039] Optionally, the lithium-loving metal element includes at least one of zinc, tin, magnesium, and aluminum. In the present invention, the introduction of a lithium-loving element into the coating can act as a bridge to guide the uniform deposition of lithium ions within the PCN-250 derivative material with a larger surface area, thereby enhancing the safety and cycling stability of lithium metal batteries.
[0040] According to the present invention, the atomic ratio of the lithium-philic metal element to the iron element in the PCN-250 derivative material can be (0.01-0.03): (0.56-1.5). In the present invention, the atomic ratio of the lithium-philic metal element to the iron element in the PCN-250 derivative material facilitates uniform deposition of lithium ions and does not affect lithium ion transport. As an example, the atomic ratio of the lithium-philic metal element to the iron element in the PCN-250 derivative material can be any of 0.01:0.56, 0.02:1, 0.03:1.5, 0.03:1, and 0.03:0.56, or any value within a range consisting of any two of the above values. In the present invention, if the atomic number ratio of the lithium-philic metal element to the iron element in the derivative material of PCN-250 is too large, it will cause too many atoms to occupy the transmission channel of lithium ions, affecting the transmission of lithium ions; if the atomic number ratio of the lithium-philic metal element to the iron element in the derivative material of PCN-250 is too small, it will cause too few lithium-philic elements to affect the uniform deposition of lithium ions, and too few iron elements will affect the formation of the derivative material of PCN-250, thereby affecting the amount of adsorbed gas.
[0041] According to the present invention, the coating may further include a binder and a conductive agent, that is, the coating includes a metal organic framework material, a binder and a conductive agent.
[0042] According to the present invention, the mass ratio of the metal organic framework material, the binder and the conductive agent in the coating can be (0.7-0.9): (0.1-0.2): (0.05-0.1). In the present invention, the appropriate mass ratio of the metal organic framework material, the binder and the conductive agent in the coating helps to form a uniform coating with a small peeling force, which can be well composited with a metal substrate such as a lithium strip. As an example, the mass ratio of the metal organic framework material, the binder and the conductive agent in the coating can be any of 0.7:0.1:0.05, 0.8:0.2:0.07, 0.9:0.2:0.1, 0.9:0.1:0.07 and 0.9:0.1:0.05 or any value within the range of any two of the above values.
[0043] Optionally, the binder comprises polyvinylidene fluoride.
[0044] Optionally, the conductive agent includes conductive carbon black.
[0045] According to the present invention, the coating may further include an anti-cracking agent, that is, the coating includes a metal organic framework material, a binder, a conductive agent and an anti-cracking agent.
[0046] According to the present invention, in the coating, the mass ratio of the metal organic framework material, the binder, the conductive agent and the anti-cracking agent can be (0.7~0.9): (0.1~0.2): (0.05~0.1): (0.05:0.1). In the present invention, the appropriate mass ratio of the metal organic framework material, the binder, the conductive agent and the anti-cracking agent in the coating helps to form a uniform coating with a small peeling force. The anti-cracking agent can avoid the problem of cracking or powdering of the metal material when compounding with the base material. As an example, the mass ratio of the metal organic framework, binder, conductive agent and anti-cracking agent in the coating can be any value among 0.7:0.1:0.05:0.05, 0.8:0.2:0.07:0.07, 0.9:0.2:0.1:0.1, 0.9:0.1:0.07:0.07 and 0.9:0.1:0.05:0.05, or any value within the range composed of any two of the above values.
[0047] Optionally, the anti-cracking agent includes a silane compound. Preferably, the silane compound includes at least one of vinyl silane, amino silane and polysiloxane.
[0048] According to the present invention, the thickness of the coating can be 5 to 50 μm. In the present invention, the appropriate coating thickness can adsorb more gas without affecting the transmission of lithium ions. As an example, the thickness of the coating can be any value among 5 μm, 10 μm, 20 μm, 30 μm, 40 μm and 50 μm, or any value within the range of any two of the above values. In the present invention, if the thickness of the coating is too thick, it will lead to the transmission of lithium ions; if the thickness of the coating is too thin, it will result in limited adsorption of gas.
[0049] Optionally, the metal substrate includes copper foil, nickel foil, lithium strip or lithium alloy composite strip; preferably, the lithium alloy composite strip includes lithium aluminum alloy composite strip, lithium magnesium alloy composite strip or lithium tin alloy composite strip.
[0050] A second aspect of the present invention further provides a method for preparing a lithium metal negative electrode sheet, comprising the following steps:
[0051] S1, mixing PCN-250 material, carboxylic acid compound, hydroxyl-containing volatile solvent and water, performing pore-forming reaction and esterification reaction to obtain PCN-250 derivative material;
[0052] S2. Prepare a slurry containing the derivative material of PCN-250, and form a coating on the base film with the slurry.
[0053] The preparation method of the lithium metal negative electrode sheet provided by the present invention uses a common hydroxyl-containing volatile solvent and water to react with PCN-250 material to form pores, and then adds a carboxylic acid compound. While the PCN-250 material forms pores, the azobenzene groups therein also react with the hydroxyl groups of the hydroxyl-containing volatile solvent to form hydroxyazobenzene. When the high-temperature reaction is carried out in a closed container, the hydroxyl-containing volatile solvent and water will evaporate at a certain temperature, and the volatilized gas cannot be discharged. The gas will expand the pores of a certain diameter. The expanded pores will absorb more gas. However, if the surface area of the PCN-250 material increases as the pores become larger, the lithium ion transmission capacity will be affected, resulting in a weakened gas adsorption capacity of the battery. Finally, the generated hydroxyazobenzene groups will also react with the carboxyl groups of the carboxylic acid compound to form ester groups (COOR'). The oxygen atom in the ester group is connected to the carbon atom through a covalent bond, making the ester azobenzene have better chemical stability.
[0054] According to the present invention, in step S1, the mass ratio of the PCN-250 material, the carboxylate, the hydroxyl-containing volatile solvent and water can be (3-8): (2-6): (6-12): (10-20). In the present invention, a suitable mass ratio of the PCN-250 material, the carboxylate, the hydroxyl-containing volatile solvent and water helps to form an appropriate amount of PCN-250 derivative material. As an example, the mass ratio of the PCN-250 material, the carboxylate, the hydroxyl-containing volatile solvent and water can be any value among 3:2:6:10, 4:3:7:12, 5:4:9:14, 6:5:10:15, 7:6:12:20 and 8:6:12:20, or any value within the range of any two of the above values.
[0055] Optionally, the carboxylic acid compound includes carboxylate and / or carboxylic acid.
[0056] Optionally, the carboxylate includes acetate, preferably, the acetate includes at least one of zinc acetate, tin acetate, magnesium acetate and aluminum acetate.
[0057] In this application, the metal in the acetate greatly improves the PCN-250' material in terms of lithium ion transport and uniform deposition, which is affected by the large surface area.
[0058] Optionally, the carboxylic acid comprises acetic acid.
[0059] Optionally, the hydroxyl-containing volatile solvent includes at least one of methanol, ethanol and propanol.
[0060] According to the present invention, in step S1, the PCN-250 material can be purchased commercially or prepared by a conventional method.
[0061] According to the present invention, in step S1, the method for preparing the PCN-250 material may include:
[0062] Mixing 3,3',5,5'-tetracarboxylazobenzene, a metal source, and a solvent to obtain a mixed solution; mixing the mixed solution with an acid compound, and performing a solvothermal reaction to obtain a PCN-250 material;
[0063] Optionally, the mass ratio of the 3,3',5,5'-tetracarboxylazobenzene to the metal source is 1:1;
[0064] Optionally, the metal source includes Fe3O(CH3COO)6;
[0065] Optionally, the solvent comprises N,N-dimethylformamide;
[0066] Optionally, the ratio of the acid compound to the 3,3',5,5'-tetracarboxylazobenzene is 10 mL:3 g;
[0067] Optionally, the acid compound includes glacial acetic acid;
[0068] Optionally, the temperature of the solvent thermal reaction is 140° C., and the time of the solvent thermal reaction is 12 h.
[0069] Optionally, in step S2, the method for preparing the slurry containing the derivative material of PCN-250 includes: stirring the derivative material of PCN-250, a binder, a conductive agent, and a solvent; or, stirring the derivative material of PCN-250, a binder, a conductive agent, an anti-cracking agent, and a solvent; optionally, the solvent includes dimethylformamide and / or N-methyl-2-pyrrolidone.
[0070] According to the present invention, in step S1, the environmental conditions of the pore-forming reaction can be a closed environment, the temperature of the pore-forming reaction can be 80-95°C, and the time of the pore-forming reaction can be 1-4 hours. As an example, the temperature of the pore-forming reaction can be any value among 80°C, 82°C, 85°C, 88°C, 90°C, 92°C and 95°C, or any value within the range consisting of any two of the above values, and the time of the pore-forming reaction can be any value among 1 hour, 2 hours, 3 hours and 4 hours, or any value within the range consisting of any two of the above values.
[0071] According to the present invention, in step S1, the temperature of the esterification reaction may be 110 to 140° C., and the time of the esterification reaction may be 2 to 4 hours. As an example, the temperature of the esterification reaction may be any value among 110° C., 115° C., 120° C., 125° C., 130° C., 135° C., and 140° C., or any value within a range consisting of any two of the above values, and the time of the esterification reaction may be any value among 2 hours, 2.5 hours, 3 hours, 3.5 hours, and 4 hours, or any value within a range consisting of any two of the above values.
[0072] According to the present invention, in step S1, after the esterification reaction is completed, a post-treatment may be further included, and the post-treatment includes: washing and drying the product obtained after the esterification reaction is completed;
[0073] The washing reagent includes ethanol;
[0074] The drying temperature is 50-80°C, and the drying time is 10-20 hours. As an example, the drying temperature can be any value among 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, and 80°C, or any value within a range consisting of any two of the above values, and the drying time can be any value among 10 hours, 12 hours, 15 hours, 18 hours, and 20 hours, or any value within a range consisting of any two of the above values.
[0075] According to the present invention, in step S2, the method of forming a coating of the slurry on the base film includes coating or transfer; the specific process of the transfer includes: the slurry is evenly coated on the surface of the transfer base film to form a slurry layer, and the transfer base film is obtained after drying; the transfer base film and the metal substrate are roller-transferred, and the metal substrate and the slurry layer are arranged relative to each other to obtain the lithium metal negative electrode.
[0076] A third aspect of the present invention provides a battery, comprising a negative electrode sheet, wherein the negative electrode sheet comprises the above-mentioned lithium metal negative electrode sheet and / or a lithium metal negative electrode sheet prepared according to the above-mentioned preparation method.
[0077] The present invention is further described in detail below by way of examples. The raw materials used in the examples can all be obtained through commercial sources.
[0078] Example 1
[0079] The method for preparing a lithium metal negative electrode sheet comprises the following steps:
[0080] (1) 3 g of 3,3',5,5'-tetracarboxylazobenzene and 3 g of Fe3O(CH3COO)6 were stirred and dispersed in 200 mL of N,N-dimethylformamide for 1 h to obtain a mixed solution; 10 mL of glacial acetic acid was mixed with the mixed solution and stirred and dispersed for 0.5 h, and then placed in a vacuum drying oven for solvent thermal reaction at 140 ° C for 12 h. After the solvent thermal reaction was completed, the obtained product was naturally cooled to room temperature, and a precipitate was obtained by filtration. It was washed alternately with ethanol and water, and finally dried at 60 ° C for 12 h to obtain PCN-250 material;
[0081] (2) 5 g of PCN-250 material, 8 mL of ethanol, 4 g of zinc acetate and 15 mL of water were mixed, and the pore-forming reaction was carried out at 85 ° C in a sealed container for 2 h, and then the temperature was raised to 120 ° C for esterification reaction for 3 h. After the esterification reaction, the obtained product was separated to obtain a lower layer solution, and the obtained lower layer solution was washed with ethanol and water, and finally dried at 60 ° C for 12 h to obtain a PCN-250 derivative material;
[0082] (3) 3 g of PCN-250 derivative material, 0.85 g of binder polyvinylidene fluoride, 0.22 g of conductive carbon black and 0.22 g of anti-cracking agent vinyl silane were mixed and ground for 20 min, and then N-methylpyrrolidone was added and ground for 30 min to obtain a slurry; the slurry was scraped onto a PET base film and dried at 60°C for 12 h to obtain a transfer base film; the transfer base film and a lithium tape were rolled together at 0.4 MPS to obtain a lithium metal negative electrode sheet.
[0083] Example 2
[0084] The method for preparing a lithium metal negative electrode sheet comprises the following steps:
[0085] (1) 3 g of 3,3',5,5'-tetracarboxylazobenzene and 3 g of Fe3O(CH3COO)6 were stirred and dispersed in 200 mL of N,N-dimethylformamide for 1 h to obtain a mixed solution; 10 mL of glacial acetic acid was mixed with the mixed solution and stirred and dispersed for 0.5 h, and then placed in a vacuum drying oven for solvent thermal reaction at 140 ° C for 12 h. After the solvent thermal reaction was completed, the obtained product was naturally cooled to room temperature, and a precipitate was obtained by filtration. It was washed alternately with ethanol and water, and finally dried at 60 ° C for 12 h to obtain PCN-250 material;
[0086] (2) 5 g of PCN-250 material, 8 mL of ethanol, 8 g of zinc acetate and 15 mL of water were mixed, and the pore-forming reaction was carried out at 85 ° C in a sealed container for 2 h, and then the temperature was raised to 120 ° C for esterification reaction for 3 h. After the esterification reaction, the obtained product was separated to obtain a lower layer solution, and the obtained lower layer solution was washed with ethanol and water, and finally dried at 60 ° C for 12 h to obtain a PCN-250 derivative material;
[0087] (3) 3 g of PCN-250 derivative material, 0.85 g of binder polyvinylidene fluoride, 0.22 g of conductive carbon black and 0.22 g of anti-cracking agent vinyl silane were mixed and ground for 20 min, and then N-methylpyrrolidone was added and ground for 30 min to obtain a slurry; the slurry was scraped onto a PET base film and dried at 60°C for 12 h to obtain a transfer base film; the transfer base film and a lithium tape were rolled together at 0.4 MPS to obtain a lithium metal negative electrode sheet.
[0088] Example 3
[0089] The method for preparing a lithium metal negative electrode sheet comprises the following steps:
[0090] (1) 3 g of 3,3',5,5'-tetracarboxylazobenzene and 3 g of Fe3O(CH3COO)6 were stirred and dispersed in 200 mL of N,N-dimethylformamide for 1 h to obtain a mixed solution; 10 mL of glacial acetic acid was mixed with the mixed solution and stirred and dispersed for 0.5 h, and then placed in a vacuum drying oven for solvent thermal reaction at 140 ° C for 12 h. After the solvent thermal reaction was completed, the obtained product was naturally cooled to room temperature, and a precipitate was obtained by filtration. It was washed alternately with ethanol and water, and finally dried at 60 ° C for 12 h to obtain PCN-250 material;
[0091] (2) 5 g of PCN-250 material, 8 mL of ethanol, 1 g of zinc acetate and 15 mL of water were mixed, and the pore-forming reaction was carried out at 85 ° C in a sealed container for 2 h, and then the temperature was raised to 120 ° C for esterification reaction for 3 h. After the esterification reaction, the obtained product was separated to obtain a lower layer solution, and the obtained lower layer solution was washed with ethanol and water, and finally dried at 60 ° C for 12 h to obtain a PCN-250 derivative material;
[0092] (3) 3 g of PCN-250 derivative material, 0.85 g of binder polyvinylidene fluoride, 0.22 g of conductive carbon black and 0.22 g of anti-cracking agent vinyl silane were mixed and ground for 20 min, and then N-methylpyrrolidone was added and ground for 30 min to obtain a slurry; the slurry was scraped onto a PET base film and dried at 60°C for 12 h to obtain a transfer base film; the transfer base film and a lithium tape were rolled together at 0.4 MPS to obtain a lithium metal negative electrode sheet.
[0093] Example 4
[0094] The method for preparing the lithium metal negative electrode sheet differs from that of Example 1 in that:
[0095] The amount of ethanol used is 12 mL.
[0096] The rest are the same as in Example 1.
[0097] Comparative Example 1
[0098] The method for preparing a lithium metal negative electrode sheet comprises the following steps:
[0099] (1) 3 g of 3,3',5,5'-tetracarboxylazobenzene and 3 g of Fe3O(CH3COO)6 were stirred and dispersed in 200 mL of N,N-dimethylformamide for 1 h to obtain a mixed solution; 10 mL of glacial acetic acid was mixed with the mixed solution and stirred and dispersed for 0.5 h, and then placed in a vacuum drying oven for solvent thermal reaction at 140 ° C for 12 h. After the solvent thermal reaction was completed, the obtained product was naturally cooled to room temperature, and a precipitate was obtained by filtration. It was washed alternately with ethanol and water, and finally dried at 60 ° C for 12 h to obtain PCN-250 material;
[0100] (2) 3 g of PCN-250 material, 0.85 g of binder polyvinylidene fluoride, 0.22 g of conductive carbon black and 0.22 g of anti-cracking agent vinyl silane were mixed and ground for 20 min, and then N-methylpyrrolidone was added and ground for 30 min to obtain a slurry; the slurry was scraped onto a PET base film and dried at 60°C for 12 h to obtain a transfer base film; the transfer base film and a lithium tape were rolled together at 0.4 MPS to obtain a lithium metal negative electrode sheet.
[0101] Comparative Example 2
[0102] The method for preparing the lithium metal negative electrode sheet differs from that of Example 1 in that:
[0103] The amount of ethanol used is 4 mL.
[0104] The rest are the same as in Example 1.
[0105] Battery preparation and electrochemical performance testing
[0106] 1. Preparation of batteries
[0107] The negative electrode sheets prepared in the above examples and comparative examples were combined with Ni90 to prepare lithium metal laminate batteries.
[0108] 2. Electrochemical performance test
[0109] (1) The volume of the fresh battery (initial volume) and the volume of the battery after cycling to 80% of the battery capacity retention rate (post-cycle volume) were tested by the buoyancy method, and the battery volume change rate was calculated: volume change rate = (initial volume - post-cycle volume) / initial volume * 100%.
[0110] The specific test method for cycling to a battery capacity retention rate of 80% is as follows: the test temperature is 25°C, the battery is connected to the charging cabinet, first charged to 4.35V with a constant current of 0.1C, let it stand for 5 minutes, then discharged to 2.8V with a constant current of 0.1C and let it stand for 5 minutes, this step is repeated twice and then let it stand for 30 minutes to complete the formation step; charged to 4.35V with a constant current of 0.33C, then charged at a constant voltage of 4.35V to a current ≤0.05C, let it stand for 5 minutes, then discharged to 2.8V with a constant current of 0.5C and let it stand for 5 minutes, and this step is repeated until the battery capacity retention rate is 80%. The test results are shown in Table 1 and Figure 1 shown.
[0111] Table 1
[0112] <![CDATA[Initial volume / cm 3 > <![CDATA[Volume after cycling / cm 3 > Volume change rate / % Example 1 45.6 57.2 25.5 Example 2 45.8 66.7 45.6 Example 3 46.2 68.5 48.3 Example 4 45.1 55.6 23.3 Comparative Example 1 44.9 72.8 62.1 Comparative Example 2 45.3 65.3 44.2
[0113] As shown in Table 1, when the zinc acetate content is 4g, the ester groups in the PCN-250 derivative material generated by its reaction with the PCN-250 material contribute to the material's chemical stability. During gas adsorption, the material undergoes no chemical changes, resulting in minimal gas production after the cycle. When the zinc acetate content is too high, the PCN-250 derivative material formed contains excess acetate ions in addition to the existing ester groups, which can affect the material's chemical stability and, in turn, its adsorption capacity, manifesting as an increase in gas production volume. When the zinc acetate content is too low, the resulting PCN-250 derivative material containing ester groups exhibits poor chemical stability, further impacting its adsorption capacity, manifesting as an increase in gas production volume.
[0114] During the pore-forming reaction, since the boiling point of ethanol is 78.3°C, it will vaporize when the reaction temperature exceeds the boiling point of ethanol. However, in a closed container, ethanol cannot evaporate, which will expand the original small pores or no pores in the PCN-250 material, causing the pores to increase, and the ability to adsorb gas will also increase accordingly. When the amount of ethanol decreases, the pores formed are not large enough or sufficient, resulting in weak adsorption capacity. However, when the amount of ethanol increases, the pores become more and more numerous, and their surface area becomes larger and larger, which in turn hinders the transmission of lithium ions. When it increases to a certain extent, most of the electrolyte will enter the pores, causing the pressure inside the pores of the PCN-250 material to be greater than the external pressure, causing the structure of the PCN-250 material to be deformed from a square to a diamond, which reduces the mechanical properties of the PCN-250 material and thus reduces the cycle performance of the battery.
[0115] After the addition of zinc acetate, before the esterification reaction, the azobenzene group will react with some of the hydroxyl groups in the ethanol to form hydroxyazobenzene. During the esterification reaction, hydroxyazobenzene will react with the carboxyl groups in the zinc acetate to form a zinc complex ester-based PCN-250 derivative material. The oxygen atom in the ester group is connected to the carbon atom through a covalent bond, which makes the ester-based azobenzene have better chemical stability, ensuring that the chemical properties of the azobenzene group will not be affected even if the structure changes from square to rhombus under pressure. In addition, the introduction of zinc ions will also greatly improve the lithium ion transmission and uniform deposition of the PCN-250 derivative material due to its large surface area.
[0116] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A lithium metal negative electrode sheet, characterized in that: The lithium metal negative electrode sheet comprises a metal substrate and a coating provided on at least one surface of the metal substrate in a thickness direction; the coating comprises a metal organic framework material; The metal organic framework material includes a PCN-250 derivative material, and the PCN-250 derivative material has an ester azobenzene group.
2. The lithium metal negative electrode sheet according to claim 1, characterized in that The porosity of the metal organic framework material is 50% to 70%, and / or The pore diameter of the metal organic framework material is 0.6-1.5 nm.
3. The lithium metal negative electrode sheet according to claim 1, characterized in that The coating further contains a lithium-philic metal element; Optionally, the lithiophilic metal element includes at least one of zinc, tin, magnesium and aluminum; Optionally, the atomic number ratio of the lithium-philic metal element to the iron element in the PCN-250 derivative material is (0.01-0.03): (0.56-1.5).
4. The lithium metal negative electrode sheet according to claim 1, characterized in that The coating also includes a binder and a conductive agent; Optionally, the mass ratio of the metal organic framework material, the binder and the conductive agent in the coating is (0.7-0.9): (0.1-0.2): (0.05-0.1); Optionally, the binder includes polyvinylidene fluoride; and the conductive agent includes conductive carbon black.
5. The lithium metal negative electrode sheet according to claim 1, characterized in that: The thickness of the coating is 5 to 50 μm.
6. A method for preparing a lithium metal negative electrode sheet, characterized in that: The following steps are involved: S1, mixing PCN-250 material, carboxylic acid compound, hydroxyl-containing volatile solvent and water, performing pore-forming reaction and esterification reaction to obtain PCN-250 derivative material; S2. Prepare a slurry containing the derivative material of PCN-250, and form a coating on the base film with the slurry.
7. The method for preparing a lithium metal negative electrode sheet according to claim 6, wherein: In step S1, the mass ratio of the PCN-250 material, the carboxylate, the hydroxyl-containing volatile solvent and water is (3-8): (2-6): (6-12): (10-20); Optionally, the carboxylic acid compound comprises a carboxylate and / or a carboxylic acid; Optionally, the carboxylate comprises acetate, preferably, the acetate comprises at least one of zinc acetate, tin acetate, magnesium acetate and aluminum acetate; Optionally, the carboxylic acid comprises acetic acid; Optionally, the hydroxyl-containing volatile solvent includes at least one of methanol, ethanol and propanol.
8. The method for preparing a lithium metal negative electrode sheet according to claim 6, wherein: In step S2, the method for preparing the slurry containing the PCN-250 derivative material includes stirring the PCN-250 derivative material, a binder, a conductive agent, and a solvent; Optionally, the solvent comprises dimethylformamide and / or N-methyl-2-pyrrolidone.
9. The method for preparing a lithium metal negative electrode sheet according to claim 6, wherein: In step S1, the environmental condition of the pore-forming reaction is a closed environment, the temperature of the pore-forming reaction is 80-95° C., and the time of the pore-forming reaction is 1-4 hours; and / or, In step S1, the temperature of the esterification reaction is 110-140° C., and the time of the esterification reaction is 2-4 hours.
10. A battery, characterized in that: The battery includes a negative electrode sheet, wherein the negative electrode sheet includes the lithium metal negative electrode sheet according to any one of claims 1 to 5 and / or the lithium metal negative electrode sheet prepared by the preparation method according to any one of claims 6 to 9.
Citation Information
Patent Citations
Three-dimensional composite lithium metal negative electrode, preparation method thereof and lithium battery
CN112750983A
Electrode plate and lithium ion battery
CN113764643A
Polycrystalline iron-containing metal organic framework membrane for nanofiltration of organic solvent
CN116888134A
Composite diaphragm, preparation method thereof and solid-state lithium metal battery
CN117638402A
Solid-state battery having a hybrid capacitor material with a metal-organic framework
US20220140422A1